A Look at the Work of the Master Artist Turgun Alimatov - Mukhammadiev Azizzhon Oblakulovich (International Journal on Integrated Education, 2022)
Any music is performed directly by a skilled musician. This article talks about one of such skilled performers, master artist Turgun Alimatov. In the process of learning the teacher's tanbur instrument, he got it from his teachers. The processes of forming their own school, skillfully mastering their knowledge, were highlighted on the basis of recent history literature.